Diagnosing monitoring and evaluation capacity in Africa - Caitlin, Blaser Mapitsa; Linda, Khumalo (African Evaluation Journal, 2018)
Since 2015, the Centre for Learning on Evaluation and Results-Anglophone Africa (CLEAR-AA) has implemented more than seven diagnostic tools to better understand monitoring and evaluation (M&E) systems in the region. Through the process of adapting global tools to make them more appropriate to an African context, CLEAR-AA has learned several lessons about contextually relevant definitions and boundaries of M&E systems.
Keywords: Diagnosing monitoring and evaluation capacity in Africa